2016
DOI: 10.3390/rs8050417
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Aerosol Fine-Mode Fraction from Intensity and Polarization Measurements by PARASOL over East Asia

Abstract: Abstract:The fine-mode fraction (FMF) of aerosol optical depth (AOD) is a key optical parameter that represents the proportion of fine particles relative to total aerosols in the atmosphere. However, in comparison to ground-based measurements, the FMF is still difficult to retrieve from satellite observations, as attempted by a Moderate-resolution Imaging Spectroradiometer (MODIS) algorithm. In this paper, we introduce the retrieval of FMF based on Polarization and Anisotropy of Reflectances for Atmospheric Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The aerosol models with the lowest three η constitute the optimal aerosol models. The concrete aerosol model parameters used in this study can be found in [8] and are presented in Table A1.…”
Section: Retrieval Of Aodmentioning
confidence: 99%
See 1 more Smart Citation
“…The aerosol models with the lowest three η constitute the optimal aerosol models. The concrete aerosol model parameters used in this study can be found in [8] and are presented in Table A1.…”
Section: Retrieval Of Aodmentioning
confidence: 99%
“…Recently, we proposed an aerosol fine-mode fraction (FMF) retrieval method [8] which uses the ratio of the fine-mode AOD (AOD f ) to the total AOD to obtain FMF. This method has been implemented on the Polarization and Anisotropy of Reflectances for Atmospheric Science coupled with Observations from a Lidar (PARASOL) platform, which has the ability to detect the intensity and polarization of radiation from multi-angle observations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as Equation (1) shows, if the surface reflectance can be determined, then the AOD can be retrieved. Aerosol retrieval algorithms have been developed for many different satellite platforms based on this principle [36]. The DT approach for estimating surface reflectance over "dark" surfaces has been widely used in aerosol retrieval and atmospheric correction.…”
Section: Theoretical Basis Of Aod Retrievalmentioning
confidence: 99%
“…When the aerosol model is determined, multiple sets of R Path , T d T u and S values can be precomputed according to pre-defined combinations of AODs and geometrical conditions using the radiative transfer model. Then, a look-up table can be established for AOD retrieval [39][40][41].…”
Section: General Principlementioning
confidence: 99%